Mini-review of capillary-gas-treating bioreactors: opportunities and challenges - Kraakman, Norbertus J. R.; Torres, Andrés F.; Sampaio, Bruna; Bordel, Sergio; Lebrero, Raquel; Muñoz, Raúl (Frontiers in Environmental Engineering, 2026)
Mass transfer in gas–liquid contactors requires energy input (e.g., mixing or pressure drop) and is a critical parameter for the design and application of process equipment. Efforts in the engineering of less energy-intensive reactors to enhance mass transfer rate are key in biological gas-liquid reactors that treat hydrophobic gaseous compounds. Mass transfer coefficients (KLa) in capillary reactors may be between one or two orders of magnitude higher than in conventional gas–liquid contactors. In this context, environmental abatement processes typically implemented in bioscrubbers or biotrickling filters, as well as industrial fermentation processes using airlift or stirred tank bioreactors containing cell cultures that are mass-transfer limited, could benefit from a capillary gas bioreactor configuration using a macro-channel (>1 mm internal diameter). This review discusses capillary reactors which can combine good mass transfer with relatively low pressure drop—two important factors affecting the cost-effectiveness of many industrial applications of biological gas treatment/processing systems.